Earth emergency [videorecording (DVD)] - Gray, Susan (Television director); Waltch, Bonnie E.; Gere, Richard, 1949-; Bstan-ʼdzin-rgya-mtsho, Dalai Lama XIV, 1935-; Thunberg, Greta, 2003- (PBS, 2022)
Listen to the scientists. That's the refrain of climate activist Greta Thunberg. Climate scientists explain how warming caused by human activity is setting in motion Earth's own natural warming mechanisms, releasing greenhouse gases into the atmosphere, and further warming the planet.